Smoking and parental communication - Ballhysa, Lidra (Richtmann Publishing, 2012)
Based on the polls organized it results that the habit of smoking is considered as the smallest problem compared to the otherones that their child might have. Comparing this problem with others issues like: attendance and school results, drugs and sex, smokingis considered as the last â€œconcernâ€ of the parents and families in general. That is because this habit is considered as a health problem ofthe individual who smokes. But the facts show that it is not like this. Smoking is not only an individual health problem. On the other handwith all the great work done, continuous campaigns, fines and laws to ban smoking, youngsters and teenagers who smoke areincreasing every day. In order to win this â€œwarâ€ (that smoking should not be started or re-started) from children and teenagers it isnecessary the help of the parent, family, but changed as a behavior. The parent and the family can be promoting and cooperatingfactors with the individual that the decision to start or ban smoking can be decided with them. A careful parent does not only tell off oftakes reprimanding measures but above all becomes a friend to overcome such a danger. A well informed parent on the way how tobehave with his/her own child is a successful path to fight the habit of smoking. The work done with parents by the school or differentNGOs which are closely related to families would bring and give more results than fussy and costly campaigns.